IMPLEMENTASI TOTAL QUALITY MANAJEMEN DI SMP MUHAMMADIYAH I DEPOK SLEMAN - Nur Hamidi (Universitas Ahmad Dahlan, 2018)
Entering the past decade, the issue of quality has always been the talk of the actual, especially in the context of education management. Recognized or not, the quality of Islamic education institutions are still largely under the quality of education in general. Various attempts have been made and many of the concepts that have been applied, but everything seemed not bring significant improvement.